IMPLEMENTASI MANAJEMEN PENGEMBANGAN SUMBER DAYA MANUSIA MI NU 52 MOROREJO - Rifqil Muslim; Andrian Gandi Wijanarko; Hadi Rohyana (Institut Daarul Qur'an Jakarta, Indonesia, 2024)
This research uses a qualitative approach. This research aims to describe, analyze and interpret good management practices, supporting and inhibiting factors for human resource development at Mororejo 52 NU Elementary School, Kendal, Central Java. The researcher's data collection process involves observation, interviews and documentation. Data analysis in this research was carried out in a narrative descriptive style in three stages: data reduction, presentation, and conclusion drawing/verification. The results of the research show that Mororejo 52 NU Elementary School manages human resources and creates a planned, structured and measurable management model in order to produce quality human resources. The human resource management model in Islamic boarding school-based schools has its own uniqueness in achieving the institution's vision. Starting from the main competencies in accordance with institutional integration and collaboration in the sustainability of human resources who always provide excellent service. Human resource management model in schools with stages of analysis, planning, implementation of HR development, implementation of integration/collaboration, and monitoring and assessment of HR.